Kidney to share - Gershun, Martha; Lantos, John D. (Culture and politics of health care work., 2021)
"A woman who decides to donate a kidney to a stranger tells her story, and a bioethicist reviews the history of ethical controversies surrounding organ donation. These different perspectives on kidney donation give the reader a sense of how this medical technology has evolved and how ethics and the law have changed to make organ donation possible"--